Analisis Kemampuan Pemahaman Konsep Ditinjau Dari Kecerdasan Logis Matematis Pada Materi Fungsi Komposisi - Vivied Eka Pratiwi; Ayu Tsurayya (Universitas Islam Ahmad Dahlan (UIAD) Sinjai, 2023)
A students' ability to understand concepts is an important part of learning mathematics. However, some students are still confused when dealing with compositional function problems that really require understand of concepts. The aim of this study to analyze the ability to understand mathematical concepts in terms of mathematical logic intelligence in the compositional function material. This research uses qualitative methods with a case study approach. The subjects used in this study were 3 students of class X MIPA with high, medium, and low levels of logic mathematical intelligence. The data in this study were collected through observation, tests, interviews, and documentation. According to the results of data analysis, it is found that students with high level of logical mathematical intelligence S-1 can meet all indicators of the ability to understand concepts of mathematics, students who had a level logical mathematical intelligence medium S-2 were only able to fulfill 3 indicators, and students who had a level of logical intelligence low S-3 is able to meet all indicators. The category of students' mathematical logical intelligence level cannot determine students' ability to understand concepts, because the results show that students with low logical intelligence understand concepts better than students who have moderate logical intelligence.